All-solid-state conductive organic polymer proton battery and preparation method thereof
By using all-solid-state conductive organic polymer and polymer/inorganic hybrid films in proton batteries, problems such as circulation stability, electrolyte corrosion and narrow temperature range of water-based proton batteries are solved, and an all-solid-state proton battery with high safety, excellent cycle stability and wide application potential are achieved.
Patent Information
- Application Number
- CN202411466195.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing water-based proton batteries have problems in circulation stability, electrolyte corrosion, leakage, and narrow temperature range, and their industrial applications are not good.
All-solid-state conductive organic polymeric substance sub-battery is used, conductive organic polymers are used as symmetric electrode materials, and polymer/inorganic hybrid films are used as proton membranes to construct all-solid-state proton batteries.
It has achieved the advantages of simple preparation process, safe and reliable use, excellent cycle stability, wide working temperature range, low raw material price and simple packaging, and has huge application potential.
Smart Images

Figure CN119581556A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid-state proton batteries, and in particular relates to an all-solid-state conductive organic polymer proton battery and a preparation method thereof. Background Art
[0002] Developing various energy storage technologies to support the use of renewable energy for power generation has been seen as a possible way to achieve carbon neutrality. With the growing demand for energy storage, solid-state batteries have become a hot spot in the development of energy storage technologies due to their high safety, high energy density and environmental friendliness. + 、Na + 、Zn 2+ Mg 2+ and Al 3+ ) as charge carriers have been widely studied and applied in batteries. However, their diffusion kinetics are limited by the large ionic radius. + ) has the smallest radius (about 0.89 fm) and the lightest weight (1.0 g·mol -1 ), it has become a unique ionic charge carrier in batteries due to its fast reaction kinetics and long-term cycling stability. Moreover, hydrogen is ubiquitous on Earth, so batteries based on proton charge carriers have the advantages of low cost and sustainable resources.
[0003] Aqueous proton batteries have aroused people's research interest. For example, CN116470109A discloses an aqueous organic-hydrogen proton battery, but the all-organic negative electrode material of the aqueous proton battery disclosed therein has a dissolution problem in the electrolyte, and a lower reduction potential relative to hydrogen precipitation, which makes the cycle stability of the battery poor. CN112531162A discloses an aqueous proton battery electrode based on nitrogen-doped conjugated porous polymers and a preparation method thereof, but the electrode material of the aqueous proton battery disclosed therein will cause the electrode material structure to expand and shrink during the embedding and extraction of protons or hydrated protons. At the same time, the acidic electrolyte proposed therein is corrosive to the battery components, the electrode-electrolyte interface compatibility, and the low-temperature performance of the battery are all facing major challenges. The proton battery constructed using graphene derivatives as electrode materials in EP3000142B1 has problems such as high price of electrode materials and harsh humidity requirements for the environment. Therefore, the technology that can industrialize aqueous proton batteries is still lackluster, and new solid-state proton batteries and related electrode materials are urgently needed to be developed. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides an all-solid-state conductive organic polymer proton battery and a preparation method thereof, which utilizes the excellent reversible redox activity and acid doping / desodoping characteristics of conductive organic polymers to select symmetrical electrode materials, and uses polymer / inorganic hybrid membranes as proton membranes to construct an all-solid-state proton battery. The all-solid-state proton battery has the advantages of simple preparation process, safe and reliable use, excellent cycle stability, wide operating temperature range, low raw material price, simple packaging, etc., and has great application potential in the field of energy storage and power batteries.
[0005] The present invention is achieved through the following technical solutions:
[0006] An all-solid-state conductive organic polymer proton battery comprises a positive electrode, a negative electrode and an all-solid-state proton membrane; the positive electrode and the negative electrode both comprise a current collector and an electrode active material layer loaded on the current collector, the electrode active material layer comprises a conductive organic polymer, a dispersant and a binder in a mass ratio of (6.75-7.5):(0.75-1.5):(1-2.5); the conductive organic polymer is one or more of a nanocomposite material formed of polypyrrole, polythiophene, polyaniline, polydioxythiophene, polyparaphenyleneethylene and carbon nanomaterials; the all-solid-state proton membrane is a polymer / inorganic hybrid membrane formed by a polymer, a functionalized inorganic nanosol and an acid at room temperature.
[0007] Preferably, the dispersant is one or more of sodium oleate, polycarboxylate, sulfonate, polyethylene glycol, and polymer-type hyperdispersant.
[0008] Preferably, the binder is one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, styrene-butadiene rubber, perfluorosulfonic acid, polyurethane, polyacrylate, and polyvinyl alcohol.
[0009] Preferably, in the all-solid proton membrane, the solid mass ratio of the polymer to the functionalized inorganic nanosol is 1:1 to 1:3.
[0010] Preferably, the polymer is one or more of polyacrylamide, polyacrylic acid, polyvinyl alcohol, chitosan, cellulose, and polyurethane.
[0011] Preferably, the functionalized inorganic nano-sol is one or more of nano-titanium dioxide, nano-silicon dioxide and nano-cerium dioxide.
[0012] Preferably, the acid is one or more of an inorganic acid and an organic acid; the inorganic acid is sulfuric acid or phosphoric acid; the organic acid is sulfosuccinic acid or dodecylbenzenesulfonic acid.
[0013] Preferably, the electrode material of the current collector is one or more of carbon paper, carbon cloth, conductive cloth, graphene felt, and stainless steel mesh.
[0014] The preparation method of the above-mentioned all-solid-state conductive organic polymer proton battery comprises the following steps:
[0015] Step 1) uniformly mixing a conductive organic polymer, a dispersant and a binder in proportion to prepare an electrode active material coating; then uniformly coating the prepared electrode active material coating on a current collector, and drying in an oven at 80° C. for 4 hours to obtain an electrode;
[0016] Step 2) mixing the polymer solution or latex, the functionalized inorganic nanosol and the acid in proportion at room temperature and stirring them uniformly to obtain a proton membrane solution; then casting the obtained proton membrane solution on a mold, and drying at room temperature to a constant weight to obtain a polymer / inorganic hybrid membrane;
[0017] Step 3) The electrodes prepared in step 1) are used as positive and negative electrodes respectively, and separated by the polymer / inorganic hybrid membrane prepared in step 2), and assembled into a battery.
[0018] The beneficial effects of the present invention are as follows:
[0019] (1) In the all-solid-state conductive organic polymer proton battery of the present invention, protons of the conductive organic polymer (positive electrode) are released during charging and diffused to the negative electrode through the solid proton membrane. During discharge, protons diffuse from the negative electrode to the positive electrode and are embedded in the positive electrode, completing the charge and discharge cycle with stable cycle.
[0020] (2) The all-solid-state conductive organic polymer proton battery of the present invention loads a conductive polymer electrode material on a carbon current collector, and the current collector and the electrode material form a π-π interaction, which can greatly reduce the charge transfer resistance and make the battery have excellent rate performance.
[0021] (3) The all-solid-state conductive organic polymer proton battery of the present invention uses an all-solid-state proton membrane to replace the diaphragm and electrolyte, which effectively solves the problems of electrolyte corrosion, leakage and narrow temperature range in aqueous proton batteries, greatly improving the safety of use and resource sustainability.
[0022] (4) The capacity of the all-solid-state conductive organic polymer proton battery of the present invention reaches the theoretical capacity of the organic polymer, demonstrating the nanocomposite effect of the carbon nanomaterial and the organic polymer in the conductive organic polymer. In addition, the battery has low manufacturing cost, simple preparation process, and is easy to mass produce and prepare, and can be widely used in the field of large-scale energy storage and power batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The mechanical properties test results of the polymer / inorganic hybrid membranes prepared in Examples 1, 3, and 4;
[0024] Figure 2 The electrochemical impedance diagrams of the all-solid-state conductive polyaniline symmetric proton batteries prepared in Examples 1 and 10;
[0025] Figure 3 Schematic diagram of electrode reaction and proton transport of the all-solid-state conductive polyaniline symmetric proton battery prepared in Example 1;
[0026] Figure 4 The all-solid-state conductive polyaniline symmetric proton battery prepared in Example 1 is 5-50 mV·s -1 Cyclic voltammetry curves at different scan rates;
[0027] Figure 5 The all-solid-state conductive polyaniline symmetric proton battery prepared in Example 1 is -1 To 1A·g -1 Electrochemical performance test results in the current density range: A is the rate charge and discharge test result diagram, and B is the rate cycle performance test result diagram;
[0028] Figure 6 The all-solid-state conductive polyaniline symmetric proton battery prepared in Example 1 is -1 Cyclic performance test results at current density. DETAILED DESCRIPTION
[0029] The present invention provides an all-solid-state conductive organic polymer proton battery, comprising a positive electrode, a negative electrode and an all-solid-state proton membrane; wherein the positive electrode and the negative electrode both comprise a current collector and an electrode active material layer loaded on the current collector, wherein the electrode active material layer comprises a conductive organic polymer, a dispersant and a binder.
[0030] According to the embodiments disclosed in the present invention, the conductive organic polymer includes one or more nanocomposite materials formed by polypyrrole, polythiophene, polyaniline, polydioxythiophene, polyparaphenyleneethylene and carbon nanomaterials (carbon nanotubes or graphene) (any conductive polymer with redox activity is acceptable). For other conductive organic polymers with proton redox activity, the all-solid-state proton battery system provided in the embodiments disclosed in the present invention is also applicable.
[0031] According to the embodiments disclosed in the present invention, the electrode active material layer further includes a binder and a dispersant;
[0032] The binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, styrene-butadiene rubber, perfluorosulfonic acid, polyurethane, polyacrylate, and polyvinyl alcohol. These binders can form films at room temperature and can be used as binders for electrode active particles.
[0033] The dispersant includes one or more of sodium oleate, polycarboxylate, sulfonate, polyethylene glycol, and polymer-type super dispersant (any dispersant that has a dispersing function for the above-mentioned conductive organic polymer).
[0034] In the embodiments disclosed in the present invention, a conductive organic polymer, a dispersant and a binder are mixed in proportion to form an electrode active material layer, wherein the mass ratio of the conductive organic polymer, the dispersant and the binder is (6.75-7.5):(0.75-1.5):(1-2.5). The use of different binders and dispersants will result in different amounts, so the ratio will vary, but as long as the ratio is within this range, the electrode active material layer obtained has good electrochemical properties.
[0035] According to the embodiments disclosed in the present invention, the electrode material of the current collector includes one or more of carbon paper, carbon cloth, conductive cloth, graphene felt, and stainless steel mesh (any acid-resistant and conductive material is acceptable).
[0036] According to the embodiments disclosed in the present invention, the all-solid-state proton membrane is a polymer / inorganic hybrid membrane formed by mixing one or more of polymers such as polyacrylamide, polyacrylic acid, polyvinyl alcohol, chitosan, cellulose, and polyurethane (these polymers can be dissolved in water or prepared into latex), and one or more of functionalized inorganic nanosols such as nano-titanium dioxide, nano-silicon dioxide, and nano-cerium dioxide (stable inorganic nanocolloids), and one or more of acids such as inorganic acids (sulfuric acid, phosphoric acid) and organic acids (sulfosuccinic acid, dodecylbenzenesulfonic acid) (any acid that can form hydrogen bonds with organic polymers and inorganic nanosols) at room temperature, wherein the solid mass ratio of the polymer to the functionalized inorganic nanosol is 1:1 to 1:3.
[0037] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] Example 1
[0039] A method for preparing an all-solid-state conductive organic polymer proton battery, the specific steps are as follows:
[0040] (1) Preparation of electrodes
[0041] Conductive polyaniline (nanocomposite material with a mass ratio of graphene to polyaniline of 1:9) was prepared using a nano sand mill and a polymer hyperdispersant to prepare an aqueous nano slurry with a solid content of 15 wt%. 10 g of the above nano slurry was added with 1.4 g of 35 wt% polyurethane latex to prepare a conductive polyaniline electrode coating.
[0042] The conductive polyaniline electrode coating was evenly coated on the conductive cloth current collector with a scraper and dried in an oven at 80°C for 4 h to obtain a conductive polyaniline electrode. The active material loading was 1 mg / cm 2 .
[0043] (2) Preparation of polymer / inorganic hybrid membranes
[0044] In a 100mL beaker, add 10g of a 10wt% polyvinyl alcohol aqueous solution, 10g of a 30wt% nano-silica sol modified with ethyl trimethylsilyl acetate and γ-glycidyloxypropyltrimethoxysilane (the surface of the functionalized inorganic nano-sol particles has methyl and epoxy functional groups), and 1.85g of phosphoric acid, and stir evenly to obtain a proton membrane solution (phosphoric acid concentration is 1 mol / L).
[0045] The proton membrane solution is cast on a polytetrafluoroethylene mold and dried at room temperature to a constant weight to obtain a polymer / inorganic hybrid membrane, i.e., an all-solid-state proton membrane.
[0046] (3) Battery assembly
[0047] The above conductive polyaniline electrode sheet is cut into 1.13 cm 2 The discs are used as positive and negative electrodes respectively, separated by a polymer / inorganic hybrid membrane, and assembled into a button battery.
[0048] Example 2
[0049] A method for preparing an all-solid-state conductive organic polymer proton battery, the specific steps are as follows:
[0050] (1) Preparation of electrodes
[0051] Conductive polyaniline (nanocomposite material with a mass ratio of graphene to polyaniline of 1:9) was prepared using a nano-sand mill and a polymer hyperdispersant to prepare an aqueous nano-slurry with a solid content of 15 wt%. 10 g of the above nano-slurry was added with 1.5 g of a 35 wt% polyvinyl alcohol aqueous solution to prepare a conductive polyaniline electrode coating.
[0052] The conductive polyaniline electrode coating was evenly coated on the graphene felt current collector with a scraper and dried in an oven at 80°C for 4 h to obtain a conductive polyaniline electrode. The active material loading was 1 mg / cm 2 .
[0053] (2) Preparation of polymer / inorganic hybrid membranes
[0054] In a 100mL beaker, add 10g of a 10wt% polyvinyl alcohol aqueous solution, 10g of a 30wt% nano-silica sol modified with ethyl trimethylsilyl acetate and γ-glycidyloxypropyltrimethoxysilane (the surface of the functionalized inorganic nano-sol particles has methyl and epoxy functional groups), and 1.85g of phosphoric acid, and stir evenly to obtain a proton membrane solution (phosphoric acid concentration is 1 mol / L).
[0055] The proton membrane solution is cast on a polytetrafluoroethylene mold and dried at room temperature to a constant weight to obtain a polymer / inorganic hybrid membrane, i.e., an all-solid-state proton membrane.
[0056] (3) Battery assembly
[0057] The above conductive polyaniline electrode sheet is cut into 1.13 cm 2 The discs are used as positive and negative electrodes respectively, separated by a polymer / inorganic hybrid membrane, and assembled into a button battery.
[0058] Example 3
[0059] A method for preparing an all-solid-state conductive organic polymer proton battery, wherein the specific preparation steps are the same as those in Example 1, except that the concentration of phosphoric acid in the proton membrane solution is 1.3 mol / L.
[0060] Example 4
[0061] A method for preparing an all-solid-state conductive organic polymer proton battery, wherein the specific preparation steps are the same as those in Example 1, except that the concentration of phosphoric acid in the proton membrane solution is 0.7 mol / L.
[0062] Example 5
[0063] A method for preparing an all-solid-state conductive organic polymer proton battery, wherein the specific preparation steps are the same as those in Example 2, except that: the electrode material of the current collector is carbon paper, and the phosphoric acid concentration in the proton membrane solution is 1.3 mol / L.
[0064] Example 6
[0065] A method for preparing an all-solid-state conductive organic polymer proton battery, wherein the specific preparation steps are the same as those in Example 1, except that the surface of the functionalized inorganic nano-sol particles carries a methyl functional group.
[0066] Example 7
[0067] A method for preparing an all-solid-state conductive organic polymer proton battery, the specific preparation steps are the same as those in Example 1, except that: the surface of the functionalized inorganic nano-sol particles has epoxy functional groups.
[0068] Example 8
[0069] A method for preparing an all-solid-state conductive organic polymer proton battery, the specific steps are the same as those of Example 2, except that: the electrode material of the current collector is conductive cloth, and the polymer in the proton membrane is replaced by polyurethane instead of polyvinyl alcohol.
[0070] Example 9
[0071] A method for preparing an all-solid-state conductive organic polymer proton battery, the specific steps are the same as those of Example 2, except that: the electrode material of the current collector is conductive cloth, and the polymer in the proton membrane is replaced by polyacrylic acid instead of polyvinyl alcohol.
[0072] Example 10
[0073] A method for preparing an all-solid-state conductive organic polymer proton battery, wherein the specific preparation steps are the same as those in Example 2, except that the electrode material of the current collector is conductive cloth.
[0074] Test Example 1
[0075] The electrochemical performance test results of the all-solid-state conductive organic polymer proton batteries prepared in Examples 1-9 are shown in Table 1 below:
[0076] Table 1 Electrochemical performance test of Examples 1-7
[0077]
[0078]
[0079] As shown in Table 1, compared with Examples 1 and 2, the current collector of Example 2 uses graphene felt, even at 5 A·g -1 It can still produce 258mAh·g -1 The specific capacity is as high as 88%, and the capacity retention rate is as high as 91% after 5000 charge and discharge cycles. This is because the graphene felt has better conductivity than the conductive cloth, which can effectively reduce the charge transfer resistance and the internal resistance in the charge and discharge cycle, and improve the charge and discharge efficiency. Similarly, compared with Examples 3 and 5, the current collector of Example 5 uses carbon paper. Since carbon paper has better conductivity, the proton battery of Example 5 shows better electrochemical performance.
[0080] Compared with Example 1, the molar concentration of phosphoric acid in the proton membrane solution was changed in Examples 3 and 4 to 1.3 M and 0.7 M respectively. The electrochemical test results of Example 4 were similar to those of Example 1, but Example 3 showed poor electrochemical performance. The capacity retention rate dropped to 71% after only 190 cycles, which is closely related to the mechanical properties of the proton membrane. Figure 1As shown in the figure, the molar concentration of phosphoric acid has a significant effect on the mechanical properties of the proton membrane. When the molar concentration of phosphoric acid is 1.3M, the proton membrane exhibits the lowest tensile strength, which makes it difficult to maintain the mechanical stability of the proton transport channel during the battery cycle.
[0081] Compared with Example 1, the proton membranes of Examples 6 and 7 respectively use methylated and epoxylated nano-silica. Example 6 exhibits the worst electrochemical performance, and Example 7 exhibits the largest initial specific capacity. This is because the epoxy groups on the surface of the nano-silica particles participate in the formation of a polymer-inorganic hybrid structure, and "O" is conducive to the formation of proton channels, thereby improving the specific capacity.
[0082] Compared with Example 2, Examples 8 and 9 changed the type of polymer in the proton membrane, using polyurethane and polyacrylic acid respectively. The prepared solid proton membrane can still transport protons, but compared with polyvinyl alcohol, the all-solid proton membrane constructed by polyurethane and polyacrylic acid has a certain decrease in specific capacity, but the rate performance and cycle stability are also very excellent. This is because the network pore sizes formed between different polymers and inorganic nanoparticles are not the same, and the composition structure of the proton membrane is different, and the formed proton channel has different transmission efficiencies for protons.
[0083] Comparing Examples 1 and 10, the effects of changing the type and amount of binder in the electrode conductive polymer coating composition on the electrochemical impedance spectroscopy are shown in FIG. Figure 2 As shown by Figure 2 It can be seen that the charge transfer resistance of Example 1 is significantly increased compared to Example 10. This is because the polyvinyl alcohol solution can more effectively bond the conductive polymer active material than the polyurethane latex, and the increase in the mass fraction of the non-conductive binder causes the increase in the charge transfer resistance. Example 10 uses polyvinyl alcohol as a binder, and the all-solid proton membrane also contains a polyvinyl alcohol component, which produces a more compatible solid-solid interface relative to Example 1. Therefore, Example 10 has a lower solution resistance. The barrier layer of Example 10 is larger than that of Example 1, indicating that the proton transmission channel inside the electrode material is less smooth than that of Example 1. This is because a stronger hydrogen bond is formed inside the active electrode material with a larger mass fraction, and the protons form a proton transmission channel through the "O" and "N" atoms.
[0084] Test Example 2
[0085] The electrochemical performance of the all-solid-state conductive organic polymer proton battery prepared in Example 1 was tested separately. The test results are as follows: Figure 4-6 shown.
[0086] like Figure 3The figure shows the electrode reaction and proton transport schematic diagram of the all-solid-state conductive polyaniline symmetric proton battery. The all-solid-state proton membrane separates the positive electrode from the negative electrode. During the charge / discharge process, the redox reaction in the conductive polyaniline is accompanied by the release and embedding of protons through the proton transport channel in the proton membrane.
[0087] like Figure 4 The figure shows the all-solid-state conductive polyaniline symmetric proton battery at 5-50 mV·s -1 The cyclic voltammetry curves over the scan rate range show a pair of redox peaks at 0.5 / 0.2V above 0V in the cyclic voltammetry curves, indicating that the all-solid-state proton battery has fast kinetic characteristics and excellent reversibility.
[0088] At 25°C, the all-solid-state conductive polyaniline symmetric proton battery was tested at 0.1 A·g -1 To 1A·g -1 The electrochemical performance of the current density range is as follows: Figure 5 shown.
[0089] The rate charge and discharge test results are as follows: Figure 5 As shown in A, at different current densities, the all-solid-state proton battery shows a clear voltage platform, even at 1A·g -1 Still has 231mAh·g -1 In addition, in the charge and discharge rate cycle test, such as Figure 5 As shown in B, when the current density increases from 1A·g -1 Restored to 0.1A·g -1 When the capacity is fully restored to the initial capacity, the all-solid-state proton battery has excellent rate performance. At different current densities, the coulombic efficiency of the all-solid-state conductive polyaniline symmetric proton battery is close to 100%, showing excellent reversibility. This shows that the all-solid-state conductive organic polymer proton battery provided by the present invention has obtained good electrochemical performance in the absence of electrolyte, showing the excellent proton transport channel of the all-solid-state proton membrane.
[0090] like Figure 6 The figure shows the all-solid-state conductive polyaniline symmetric proton battery at 0.1 A·g -1 The cycle performance test results under the rate are shown in Figure 2. When the battery charge and discharge current is 0.1A·g -1 The reversible specific capacity of the battery is about 282 mAh g -1 After 500 cycles, the reversible specific capacity of the battery increased to 289 mAh g -1 , that is, the initial capacity retention rate reaches 102%, and the Coulombic efficiency is 100%, indicating that the all-solid-state conductive polyaniline symmetric proton battery has excellent cycle stability.
[0091] The experimental results of this test example show that the all-solid-state conductive polyaniline symmetric proton battery prepared in Example 1 has the characteristics of long cycle life and excellent rate performance.
[0092] The embodiments described above are only some embodiments of the present invention, rather than all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. The scope of protection of the present invention shall be subject to the scope required by the claims. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work shall fall within the scope of protection of the present invention.
Claims
1. An all-solid-state conductive organic polymer proton battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an all-solid-state proton membrane; the positive electrode and the negative electrode both comprise a current collector and an electrode active material layer loaded on the current collector; the electrode active material layer comprises a conductive organic polymer, a dispersant and a binder in a mass ratio of (6.75-7.5):(0.75-1.5):(1-2.5); the conductive organic polymer is one or more of nanocomposite materials formed by polypyrrole, polythiophene, polyaniline, polydioxythiophene, polyparaphenyleneethylene and carbon nanomaterials; the all-solid-state proton membrane is a polymer / inorganic hybrid membrane formed by a polymer, a functionalized inorganic nanosol and an acid at room temperature.
2. The all-solid-state conductive organic polymer proton battery according to claim 1, characterized in that: The dispersant is one or more of sodium oleate, polycarboxylate, sulfonate, polyethylene glycol, and polymer-type super dispersant.
3. The all-solid-state conductive organic polymer proton battery according to claim 1, characterized in that: The binder is one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, styrene-butadiene rubber, perfluorosulfonic acid, polyurethane, polyacrylate, and polyvinyl alcohol.
4. The all-solid-state conductive organic polymer proton battery according to claim 1, characterized in that: In the all-solid proton membrane, the solid mass ratio of the polymer to the functionalized inorganic nano-sol is 1:1 to 1:
3.
5. The all-solid-state conductive organic polymer proton battery according to claim 1, characterized in that: The polymer is one or more of polyacrylamide, polyacrylic acid, polyvinyl alcohol, chitosan, cellulose and polyurethane.
6. The all-solid-state conductive organic polymer proton battery according to claim 1, characterized in that: The functionalized inorganic nano-sol is one or more of nano-titanium dioxide, nano-silicon dioxide and nano-cerium dioxide.
7. The all-solid-state conductive organic polymer proton battery according to claim 1, characterized in that: The acid is one or more of an inorganic acid and an organic acid; the inorganic acid is sulfuric acid or phosphoric acid; the organic acid is sulfosuccinic acid or dodecylbenzenesulfonic acid.
8. The all-solid-state conductive organic polymer proton battery according to claim 1, characterized in that: The electrode material of the current collector is one or more of carbon paper, carbon cloth, conductive cloth, graphene felt, and stainless steel mesh.
9. A method for preparing an all-solid-state conductive organic polymer proton battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1) uniformly mixing a conductive organic polymer, a dispersant and a binder in proportion to prepare an electrode active material coating; then uniformly coating the prepared electrode active material coating on a current collector, and drying in an oven at 80° C. for 4 hours to obtain an electrode; Step 2) mixing the polymer solution or latex, the functionalized inorganic nanosol and the acid in proportion at room temperature and stirring them uniformly to obtain a proton membrane solution; then casting the obtained proton membrane solution on a mold, and drying at room temperature to a constant weight to obtain a polymer / inorganic hybrid membrane; Step 3) The electrodes prepared in step 1) are used as positive and negative electrodes respectively, and separated by the polymer / inorganic hybrid membrane prepared in step 2), and assembled into a battery.
Citation Information
Patent Citations
Aqueous proton battery electrode based on aza-conjugated porous polymer and preparation method thereof
CN112531162A
Aqueous organic-hydrogen proton battery
CN116470109A
Proton-battery based on graphene derivatives
EP3000142B1
Polymer / inorganic composite solid proton membrane and preparation method and application thereof
CN118630340A
All-solid-state-supercapacitor and a process for the fabrication thereof
US20160055983A1